Pelatihan dan Penerapan Pembuatan Modifikasi Sarana Net Empat dalam Pembelajaran Pendidikan Jasmani - Sumarsono, Adi; Syamsudin, Syamsudin; Wasa, Carolus (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
Providing students to go directly to teaching practice in schools is not enough to be equipped with theory and practice in the field. The knowledge gained in college must also be supported by students' skills in providing facilities and infrastructure for field practice. Through a combination of skills improvement and skills expected to be better and alert in the learning process at the School. This activity is an effort to equip students majoring in Physical Education and Recreation before taking the Field Experience Practice (PPL) program. The method used in this training uses training and application. The training process provided in the form of theory in the classroom and the application is carried out directly in the guided field. The application consists of making modifications to the means of the four nets as well as the direct practice of use in the game. The results obtained from this activity are the knowledge, skills and abilities of students to improve, this can be seen in the results prepared by students